2014
DOI: 10.1007/s00228-014-1793-8
|View full text |Cite
|
Sign up to set email alerts
|

Does age modify the relationship between adherence to secondary prevention medications and mortality after acute myocardial infarction? A nested case-control study

Abstract: The beneficial effect of evidence-based polytherapy on mortality following AMI is observed also in older populations. Nevertheless, the risk-benefit ratio associated with antiplatelet therapy is less favorable with increasing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…Thus, our findings suggest that long-term adherence to ACEI/ARBs and statins may be more important than adherence to beta-blockers after AMI. Prior, smaller studies from the United States (1,21) and other countries (3,9,22) also showed larger reductions in all-cause mortality for adherence to statins and ACEI/ARBs than adherence to beta-blockers. Accordingly, in a large observational study (>44,000 patients), beta-blockers were not associated with mortality benefit in patients with prior MI or those without a history of AMI (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our findings suggest that long-term adherence to ACEI/ARBs and statins may be more important than adherence to beta-blockers after AMI. Prior, smaller studies from the United States (1,21) and other countries (3,9,22) also showed larger reductions in all-cause mortality for adherence to statins and ACEI/ARBs than adherence to beta-blockers. Accordingly, in a large observational study (>44,000 patients), beta-blockers were not associated with mortality benefit in patients with prior MI or those without a history of AMI (23).…”
Section: Discussionmentioning
confidence: 99%
“…Many seem to do so already during the first 6 months (6). Studies from other countries also suggest sub-optimal adherence to preventive therapies for the secondary prevention of cardiovascular disease (CVD) (79). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Good adherence to polytherapy is associated with lower mortality. 29 The risk reduction associated with antiplatelet therapy was reported to decline, however, at the age of 70-75 years. 20 The polypharmacy persistence is also lower in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies focussed on a wide range of disease areas including pulmonary diseases, osteoporosis, depression, cardiovascular diseases, Parkinson's disease, epilepsy, chronic kidney disease, cancer and diabetes mellitus . Two studies did not measure disease‐specific medication (non‐)adherence .…”
Section: Resultsmentioning
confidence: 99%